Significance of National Spatial Planning for Economic Development of Secondary Cities in India: Critical Analysis of JNNURM Programme - Saima Kalwar (Sukkur IBA University, 2021)
Secondary cities are the vital economic link along with megacities in the system of cities of a nation. Whereas spatial planning and local economic development are the major factors in fostering the regional and national economic development. If the national spatial planning strategies failed to improve economic functions and linkages in the system of cities at a secondary cities level, the disparities among the regions will increase. This can result in a lagging regional economy. Therefore, the national government should develop innovate approaches to stimulate and manage the development of secondary cities. The main purpose of the paper was to critically review the spatial planning strategies carried out at the national level in the developing world. The selection of India as a case study country is based on population density and the presence of a vast network of secondary cities. The paper had critically reviewed the spatial planning strategies carried out in JNNURM national Programme to strengthen the local economic development of secondary cities during 1995-2015. The secondary data collection resources like research papers, reports and books were used to gather the required data. The results revealed that the JNNURM had focused only on the development of cluster secondary cities around megacities in order to reduce congestion and accommodate the rural immigrants. Unfortunately, the JNNURM neglected the sub-national (regional headquarter) secondary cities, which are vital players for regional economic development. Therefore, it was suggested that the Indian government should also initiate spatial planning strategies and programmes for the local economic development of sub-national secondary cities to achieve dual benefits: balanced regional and national economic development and balanced system of cities.